Isotopic composition of convective rainfall in the inland tropics of Brazil - Dos Santos, Vinicius [UNESP]; Gastmans, Didier [UNESP]; Durán-Quesada, Ana María; Sánchez-Murillo, Ricardo; Rozanski, Kazimierz; Kracht, Oliver; De Assis Quintão, Demilson [UNESP] (Copernicus Publications, 2024)
Strong convective systems characterize the tropical central-southern region of Brazil. These systems provide abundant water supply for agroindustrial activities and pose flood risks to large cities. Here, we present high-frequency (2-10 min; inter- and intra-event) rainfall isotopic compositions (n D 90 samples) to reveal regional and local atmospheric processes controlling the isotopic variability of convective systems between 2019-2021. Inter-event rainfall weighted-average (dwgd) values were low (d18Owgd = -10.0%) due to the higher rainfall along the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model trajectories from the Amazon forest during the summer. In contrast, during autumn and spring seasons HYSPLIT model trajectories from the Atlantic Ocean and southern Brazil exhibited lower rainfall amounts, resulting in high d18Owgd = -4.2%. This strong regional dwgd pattern often masks intra-event isotopic variability. Therefore, we analyzed the vertical structure of local rainfall using reflectivity (Z) from microradar data. Variations in Z indicate that microphysical processes as raindrops fall led to changes in d18O and deuterium excess (dexcess). Our findings establish a novel framework for evaluating the meteorological controls on the isotopic variability of convective precipitation in tropical South America, fill the gap in high-frequency studies in this region, and generate an isotopic dataset for convective model evaluations.